Creativity in the Arts and Science - Shea, William R. (Vitruvian Cogitationes, 2022)
Only a very rash person would attempt to define creativity in either the arts or science, let alone in both. There is no known recipe for creativity, no magic formula that opens the sluices of originality and guarantees a steady flow of new ideas and fresh insights. Indeed, we do not even know whether creativity is all kind and whether it can be meaningfully discussed under one general category. All we can legitimately do is describe creativity as it is manifested in various fields of human endeavour, from the creation of a beautiful poem to the invention of a new scientific theory. We tackle this problem in the first part of this article; in the second, we take a closer look at artistic and literary representation of science in Europe from the Renaissance to the Romanticism, and, in the third part, we examine the current situation.